Ausencia parental y su influencia en la inteligencia emocional de los adolescentes del Sector San Jacinto del cantón Buena Fe, Provincia de Los Ríos - Montes Ayala, Jacsely Andreina (2024)
The research focuses on how does parental absence affect the emotional intelligence of adolescents in the San Jacinto sector of the Buena Fe canton, province of Los Ríos? To develop the research, the main objective was to determine the incidence of parental absence on the emotional intelligence of adolescents in the San Jacinto sector of the Buena Fe canton, province of Los Ríos. In relation to the methodology, the type of research was established, focused on field research, under a descriptive design and a quantitative approach. The population considered for addressing this investigation was 100 people who live in the San Jacinto de Buena Fe sector, belonging to the Buena Fe canton, province of Los Ríos. The calculated sample was 80 people. The established techniques were the survey and psychometric tests. The instruments were the questionnaire, the Emotional Intelligence test and the ZICAP Scale Questionnaire. Among the most relevant results, it is evident that the majority of adolescents do not feel trust with their parents, in addition, it is the father who is most absent as a result of divorces. Adolescents take refuge in their friends mostly in situations of sadness or conflict. In the parental absence test, a significant lack of participation, support and communication with the absent parent is perceived. However, in terms of feeling emotionally safe, there is a more neutral perception, which could indicate that there is some factor or situation that provides the person with a certain degree of emotional security.